Benzohydrazide and Phenylacetamide Scaffolds: New Putative ParE Inhibitors - Yele, Vidyasrilekha; Sanapalli, Bharat Kumar Reddy; Wadhwani, Ashish D.; Mohammed, Afzal Azam (Frontiers in Bioengineering and Biotechnology, 2021)
Antibacterial resistance (ABR) is a major life-threatening problem worldwide. Rampant dissemination of ABR always exemplified the need for the discovery of novel compounds. However, to circumvent the disease, a molecular target is required, which will lead to the death of the bacteria when acted upon by a compound. One group of enzymes that have proved to be an effective target for druggable candidates is bacterial DNA topoisomerases (DNA gyrase and ParE). In our present work, phenylacetamide and benzohydrazides derivatives were screened for their antibacterial activity against a selected panel of pathogens. The tested compounds displayed significant antibacterial activity with MIC values ranging from 0.64 to 5.65 μg/mL. Amongst 29 title compounds, compounds 5 and 21 exhibited more potent and selective inhibitory activity against Escherichia coli with MIC values at 0.64 and 0.67 μg/mL, respectively, and MBC at onefold MIC. Furthermore, compounds exhibited a post-antibiotic effect of 2 h at 1× MIC in comparison to ciprofloxacin and gentamicin. These compounds also demonstrated the concentration-dependent bactericidal activity against E. coli and synergized with FDA-approved drugs. The compounds are screened for their enzyme inhibitory activity against E. coli ParE, whose IC50 values range from 0.27 to 2.80 μg/mL. Gratifyingly, compounds, namely 8 and 25 belonging to the phenylacetamide series, were found to inhibit ParE enzyme with IC50 values of 0.27 and 0.28 μg/mL, respectively. In addition, compounds were benign to Vero cells and displayed a promising selectivity index (169.0629–951.7240). Moreover, compounds 1, 7, 8, 21, 24, and 25 (IC50: <1 and Selectivity index: >200) exhibited potent activity in reducing the E. coli biofilm in comparison with ciprofloxacin, erythromycin, and ampicillin. These astonishing results suggest the potential utilization of phenylacetamide and benzohydrazides derivatives as promising ParE inhibitors for treating bacterial infections.